2011
DOI: 10.1074/jbc.m111.271072
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Neural Retina Leucine Zipper (NRL) Controls Photoreceptor-specific Expression of Myocyte Enhancer Factor Mef2c from an Alternative Promoter

Abstract: Background: Mef2c gene expression is significantly diminished in the retinas of NRL (neural retina leucine zipper) knockout mice. Results: NRL binding, RNA polymerase II association, and acetylation of histone H3, revealed a novel alternate Mef2c promoter. Conclusions: Activation of the retinal Mef2c promoter is NRL-dependent and specific to rod photoreceptor cells. Significance: Mef2c represents a novel regulatory node downstream of NRL in adult rod photoreceptor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
(73 reference statements)
2
34
2
Order By: Relevance
“…Consistent with previous observations (Hao et al, 2011; Hao et al, 2014), we identified several rod-specific alternative transcript isoforms that are regulated by NRL. Hematopoietic cell-specific Lyn substrate 1 ( Hcls1 ), associated with gene regulation in the hematopoietic system (Skokowa et al, 2012), exhibited rod-specific, late onset expression of a transcript which is initiated upstream of exon 8 from a new transcription start site, suggesting alternative promoter usage (Figure 6C).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous observations (Hao et al, 2011; Hao et al, 2014), we identified several rod-specific alternative transcript isoforms that are regulated by NRL. Hematopoietic cell-specific Lyn substrate 1 ( Hcls1 ), associated with gene regulation in the hematopoietic system (Skokowa et al, 2012), exhibited rod-specific, late onset expression of a transcript which is initiated upstream of exon 8 from a new transcription start site, suggesting alternative promoter usage (Figure 6C).…”
Section: Resultssupporting
confidence: 91%
“…A vast majority (672 out of 803) of TF-encoding transcripts was present in modules A, B and C, which included all known rod-specific transcriptional regulators (Figure S5). Analysis of module A yielded a sub-cluster of 12 TFs including Esrrb and Mef2C (Figure S5; Rod cluster), which are known regulators of rod differentiation (Hao et al, 2012; Hao et al, 2011; Onishi et al, 2010). The ‘rod cluster’ exhibited a clear shift in expression between P6 and P10, with no or low expression in the early postnatal days and a substantially higher expression by P10 and later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EMSAs were performed as previously described (60). The method used for this study is described in the Supplemental Methods.…”
Section: Discussionmentioning
confidence: 99%
“…OTX2, RORβ, BLIMP1 (PRDM1) and CRX are among the regulatory proteins that are crucial for photoreceptor development ; however, two key transcription factors -NRL and TRβ2 (encoded by Thrb) -together determine the generation of three distinct types of photoreceptors (rods, S-cones and M-cones) from postmitotic precursors (Ng et al, 2011). Downstream targets of NRL and CRX, as well as signaling proteins that modify their activity, further modulate the expression of photoreceptor genes (Oh et al, 2008;Onishi et al, 2009;Onishi et al, 2010;Roger et al, 2010;Hao et al, 2011). Loss or altered function of these regulatory proteins results in photoreceptor dysfunction and retinal diseases Wright et al, 2010).…”
Section: Introductionmentioning
confidence: 99%